2002
DOI: 10.1149/1.1506164
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxygen Reduction on Pt Microelectrode with Polymer Electrolytes of Various Exchange Capacities

Abstract: In order to obtain an improved design of a polymer electrolyte fuel cell cathode, the oxygen reduction reaction on a Pt microelectrode with proton exchange membranes of various exchange capacities has been investigated. The measurements were performed by chronoamperometry for determination of the diffusion coefficient and oxygen solubility, and by slow scan voltammetry for reaction kinetics with the microelectrode in the temperature range 20 to 70°C. The results of chronoamperometry and slow scan voltammetry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 21 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…As opposed to the Parthasarathy's study, 35 the inhibition was not attributed to impurities, but rather to the dehydration of Nafion at elevated temperatures and the resultant blocking of the Pt surface by the hydrophobic component of Nafion. A similar suggestion was also put forward by Mitsushima and coworkers, 43 who explained the suppression of hydrogen adsorption/desorption on Pt UME pressed against different ionomeric membranes by the blocking of Pt surface sites by the hydrophobic component of the ionomer. The already complex issue of Nafion surface morphology is additionally complicated by the various effects of materials in contact with the ionomer surface.…”
supporting
confidence: 74%
“…As opposed to the Parthasarathy's study, 35 the inhibition was not attributed to impurities, but rather to the dehydration of Nafion at elevated temperatures and the resultant blocking of the Pt surface by the hydrophobic component of Nafion. A similar suggestion was also put forward by Mitsushima and coworkers, 43 who explained the suppression of hydrogen adsorption/desorption on Pt UME pressed against different ionomeric membranes by the blocking of Pt surface sites by the hydrophobic component of the ionomer. The already complex issue of Nafion surface morphology is additionally complicated by the various effects of materials in contact with the ionomer surface.…”
supporting
confidence: 74%
“…The orr at Ptjsolid polymer electrolyte interfaces and its associated mass transport parameters within the electrolyte medium are therefore active areas of study because of their relevance to PEMFCs. Microelectrode techniques are useful ex situ methods to characterize such interfaces [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Chronoamperometry (CA) has been used to determine the solubility and diffusion coefficient of oxygen at Ptjionomer interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ayad et al [33] reported roughness factors on smooth Pt of ∼3 while Ho and Piron [34], in their study of surface area determination of Pt in KOH, summarized roughness factors for 'bright Pt wire' determined by three different methods, in both 5 M KOH and 0.5 M H 2 SO 4 , and showing good agreement, 'r' values ranging from 1.7 ± 0.0 to 1.8 ± 0.1. Mitsushima et al [35], from their work with a Pt disk microelectrode on Nafion, reported roughness factors from 1.5 to 1.8. Parthasarathy et al [36], for a 100 m diameter Pt wire electrode, reported 'apparent roughness factors' of 9.2 for a Pt/Nafion combination and 9.6 for a Pt/H 3 PO 4 combination.…”
Section: The Electrode Catalystmentioning
confidence: 99%